Correlations of insulin function with levels of adipocyte fatty acid-binding protein and serum uric acid in patients with newly diagnosed type 2 diabetes mellitus and abdominal obesity - Sun, Xueli; Sun, Xuefang (Progress in Nutrition, 2021)
Aim: To explore the correlations of insulin function with the levels of adipocyte fatty acid-binding protein (A-FABP) and serum uric acid (SUA) in patients with newly diagnosed type 2 diabetes mellitus (T2DM) with abdominal obesity. Methods: A total of 218 newly diagnosed T2DM patients were divided into abdominal obesity (n=98) and non-abdominal obesity groups (n=120) according to waist circumference. Their baseline clinical data, laboratory indices, A-FABP and SUA levels, homeostasis model assessment of insulin resistance (HOMA-IR) and HOMA-β were compared. The correlations of HOMA-IR with A-FABP, SUA levels and HOMA-β were subjected to Pearson’s analysis. The risk factors for IR were explored by logistic regression analysis. Results: The abdominal obesity group had significantly higher body mass index (BMI), waist circumference, waist-to-hip ratio, diastolic blood pressure and systolic blood pressure than those of non-abdominal obesity group (P